Effects of applying external cold and vibration to children during vaccination on pain, fear and anxiety - Eda Sapçi; Elif Bilsin Kocamaz; Zeynep Gungormus (Elsevier, 2021)
Objectives: This study aimed to evaluate the effectiveness of the application of external cold and vibration on children experiencing pain, fear and anxiety during vaccination. Design and setting: This randomized controlled, experimental study was conducted in primary schools selected within the scope of school immunization days by a community health center. The study population consisted of first grade students who were scheduled to receive a booster dose of diphtheria, tetanus, and acellular pertussis, inactivated poliovirus vaccine (DTaP-IPV) vaccine within the scope of the school immunization program of the said community health center and the study sample consisted of 90 students (experimental: 45, control:45). Main outcome measures: In the experimental group, a device that applies external cold and vibration (Buzzy®) was placed on the injection site for 30 s before administration of the vaccine. The device was then placed above the injection site and kept there during the injection. No intervention was made during the injections in children included in the control group. The same nurse administered the injections in the experimental and control groups. Results: In the current study, it was found that there was a statistically significant difference between the experimental group and the control group in terms of the children's pain, the nurse's pain, the nurse's fear and the children's anxiety (p < 0.05), but no statistically significant difference in terms of the children's fear (p > 0.05). Conclusions: It was concluded that applying external cold and vibration during vaccination has an effect on the level of children's pain and anxiety.